Guilt, shame, and apologizing behavior: A laboratory study. (1st December 2018) - Chrdileli, Mariam; Kasser, Tim
Abstract: Studies show that people's proclivity to apologize is positively associated with dispositional guilt and negatively associated with dispositional shame, but apologizing in those studies was assessed via self-report. The current study therefore developed a means of systematically coding participants' apologizing behavior in a laboratory-based situation that provided participants with an opportunity to actually apologize (or not). Specifically, after completing measures of dispositional guilt and shame, undergraduates were deceived into thinking that they were late to the study; two observers then coded the extensiveness of the participants' apologizing behaviors. Apologizing behavior was significantly positively correlated with dispositional measures of both Guilt-Repair and Guilt-Negative-Behavior-Evaluation, was marginally positively correlated with Shame-Negative-Self-Evaluation, and was unrelated to Shame-Withdraw. These findings provide further support to theories which propose that guilt motivates apology, but raise questions about the role of shame in apologizing behavior.